The effect of the cosmic web on galaxy evolution in RESOLVE-A - Hoosain, Munira (Department of Astronomy, 2022)
Galaxy environment plays a significant role in galaxy evolution. While most work has focused on the effect of cluster and group environment, large scale structures, such as filaments and voids, may provide additional contributions. Recently, various authors have found correlations between galaxy morphology, stellar mass and colour, and the distance to cosmic web filaments in both simulations and data. However, the effect of filaments on the gas supply of galaxies is still under investigation due to conflicting results. I use data from the Resolved Spectroscopy of a Local Volume (RESOLVE) survey, which is a low-redshift galaxy census complete down to log M?/M= 8.9, to study the relationship between galaxy properties and the cosmic web. I use the Discrete Persistence Structures Extractor (DisPerSE), a topology-based software package, to map filaments in the RESOLVEA field. This work shows that galaxies in RESOLVE-A have, higher stellar masses close to filaments. When accounting for the additional effect of groups, I find no variation in the colour of galaxies with respect to their distance to filament. Low-mass (log M?/M< 9.7) galaxies increase in gas fraction with increasing distance to filament, which may indicate that low-mass galaxies lose gas as they enter filaments.